Identification of genetic targets in acute myeloid leukaemia for designing targeted therapy. (6th October 2020) - Mason, Clinton C.; Fiol, Carme R.; Baker, Monika J.; Nadal‐Melsio, Elisabet; Yebra‐Fernandez, Eva; Bicalho, Luciana; Chowdhury, Avirup; Albert, Michael; Reid, Alistair G.; Claudiani, Simone; Apperley, Jane F.; Khorashad, Jamshid S.
Summary: Few effective therapies exist for acute myeloid leukaemia (AML), in part due to the molecular heterogeneity of this disease. We sought to identify genes crucial to deregulated AML signal transduction pathways which, if inhibited, could effectively eradicate leukaemia stem cells. Due to difficulties in screening primary cells, most previous studies have performed next‐generation sequencing (NGS) library knockdown screens in cell lines. Using carefully considered methods including evaluation at multiple timepoints to ensure equitable gene knockdown, we employed a large NGS short hairpin RNA (shRNA) knockdown screen of nearly 5 000 genes in primary AML cells from six patients to identify genes that are crucial for leukaemic survival. Across various levels of stringency, genome‐wide bioinformatic analysis identified a gene in the NOX family, NOX1, to have the most consistent knockdown effectiveness in primary cells ( P  = 5∙39 × 10 −5, Bonferroni‐adjusted), impacting leukaemia cell survival as the top‐ranked gene for two of the six AML patients and also showing high effectiveness in three of the other four patients. Further investigation of this pathway highlighted NOX2 as the member of the NOX family with clear knockdown efficacy. We conclude that genes in the NOX family are enticing candidates for therapeutic development in AML.